The Timing and Substance of Divestiture Announcements: Individual, Simultaneous and Cumulative Effects - Klein, April (Journal of Finance, 1986)
This paper examines differences in announcement day effects among firms engaged in voluntary sell-offs. While, on average, an initial sell-off announcement results in a significant positive excess return, not all divestiture announcements are accompanied by positive price movements. Dividing the sample into two subsamples based on whether the transaction price is announced shows that the announcement day effect is significantly positive for the price group but not statistically different from zero for the no-price group. In addition, a positive relation is found between the relative size of the sell-off and the announcement day return.